Click Chemistry on Solid Support: Synthesis of a New REM Resin and Application for the Preparation of Tertiary Amines - Löber, Stefan; Gmeiner, Peter (Tetrahedron, 2004)
1,3-Dipolar cycloaddition was employed for the synthesis of a highly practical REM resin. Exploiting this concept, the resulting triazolylmethyl acrylate (TMA) resin was used for an efficient parallel synthesis of tertiary amines by Michael addition, subsequent quarternization and cleavage by means of β-elimination. © 2004 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2004.nat.dchph.lphch.clickc
Keywords: 1; 3-Dipolar cycloaddition; Click chemistry; REM Resin; SPOS